Sheet-like and tubular aggregates of protein nanofibril–phosphate hybrids. Issue 3 (12th December 2018) - Han, Xiangsheng; Lv, Lili; Li, Mingjie; You, Jun; Wu, Xiaochen; Li, Chaoxu
Abstract : Nanofibrils assembled by bovine serum albumin aligned into microtubes and nanosheets upon heating and cooling its solution in phosphate buffer. Abstract : Bovine serum albumin assembled into supramolecular fibrils and aligned into microtubes and nanosheets upon simply heating and cooling its solution in phosphate buffer under carefully-selected conditions. This unique "one-batch" synthesis was justified by the one-dimensional growth of phosphate crystals in combination with the strong affinity of phosphate ions to protein fibrils.